Aditya Solarwind Particle EXperiment (ASPEX) onboard the Aditya-L1 mission. (15th November 2018) - Goyal, S.K.; Kumar, P.; Janardhan, P.; Vadawale, S.V.; Sarkar, A.; Shanmugam, M.; Subramanian, K.P.; Bapat, B.; Chakrabarty, D.; Adhyaru, P.R.; Patel, A.R.; Banerjee, S.B.; et al.
Abstract: The Aditya Solarwind Particle EXperiment (ASPEX) is one of the seven scientific payloads onboard the Aditya-L1 mission (the forthcoming Indian solar mission), to be placed in a halo orbit around the L1 Lagrangian point of the Sun-Earth system, at a distance of 1.5 million km from the Earth, along the Sun-Earth line. ASPEX will carry out the in-situ, multi-directional measurements of the slow and fast solar wind; suprathermal particles and solar energetic particles in the energy range of 100 eV/n to 20 MeV/n. Multi-directional measurements from ASPEX will help in understanding the anisotropy in the energy distribution of particles arriving from different directions. The ASPEX payload will play a significant role in the understanding of the acceleration mechanism and generation of these energetic particles in the interplanetary medium. The ASPEX instrument has been configured as two sub-systems viz . the Solar Wind Ion Spectrometer and the SupraThermal & Energetic Particle Spectrometer. This paper presents the configuration details of both the sub-systems along with preliminary results obtained from the breadboard models. Highlights: Aditya Solarwind Particle EXperiment (ASPEX), one of the seven scientific experiments onboard the Aditya-L1 mission. He ++ and H + measurements in the energy range of 100 eV to 20 MeV/n. Simultaneous measurements of the solar wind and the solar energetic particles with directional information.